Os Capões de Mata da Cadeia do Espinhaço: padrões e processos ecológicos - Marcel Serra Coelho (2014)
The purpose of this study was to describe the capões associated to the Espinhaço Range under the perspective of the landscape context in which they are inserted. The structure, composition and reproductive aspects of the vegetation in addition to their soil properties are also analyzed. Capões of the Espinhaço Range have a similar floristic composition to the semideciduous forests from southeastern Brazil, those associated to the Atlantic Forest domain, despite having been classified in its climate regime as an ombrophilous vegetation. Capões of the Espinhaço Range are classified as disjunctions of broadleaved, evergreen, cloud, montane tropical forest located on mountain ridges, rupicolous slopes or swamp. Capões are always associated to mountains which concentrate rainfall and cloudiness. They are also strongly influenced by elements of Atlantic Rain Forest despite the elements of Cerrado are present in minor proportions, these increasing their influence according to the levels of disturbance suffered by the vegetation. Capões are an edaphoclimatic formation, hence dependent on specific climate and soil properties for their development. Soil physical properties, such as drainage, are more relevant than their chemical properties, like nutrient input, to the establishment and development of the capões. Among the several threats, fire stands to cause dimension decreases and changes in the successional dynamics of the capões. The capões are located in a ecological transition zone. They are natural islands mostly imersed in matrices of opened fields, hence having a high biogeographical importance, emerging as a conservation priority.